2005
DOI: 10.1073/pnas.0507802102
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin crouches to sprint but resists pushing

Abstract: Recent optical trap experiments have applied resisting, assisting, and sideways loads to conventional kinesin moving on microtubules at fixed [ATP]. To gain insight into intermediate motions when the motor protein takes its 8.2-nm steps, the velocity and randomness data have been analyzed by using discrete-state stochastic models with a three-dimensional ''energy landscape.'' The bead size and tether angle play a crucial role. The analysis implies that on binding ATP the motor ''crouches,'' the point of attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 22 publications
(28 reference statements)
7
104
1
Order By: Relevance
“…Such a freely jointed chain is expected to be very flexible and would be stretched to nearly its contour length in optical tweezer experiments (34). Our method should allow us to directly measure such molecular deformations that might influence the mechanochemistry of kinesin (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Such a freely jointed chain is expected to be very flexible and would be stretched to nearly its contour length in optical tweezer experiments (34). Our method should allow us to directly measure such molecular deformations that might influence the mechanochemistry of kinesin (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…As our model shows, electrostatic effects combined with a modulation of the barriers for proton transfer are sufficient to achieve the gating required for highly efficient proton pumping. The mechanisms identified here for energy transduction by using redox chemistry may also be useful in studies of other molecular machines (24) and may aid in the design of novel bio-inspired fuel cells.…”
Section: Effects Of D Channel Mutationsmentioning
confidence: 99%
“…Only the key redox and proton sites are retained, with the effects of the other sites absorbed into effective free energies and rate coefficients in a master equation that governs the dynamics. Master equations provide a powerful framework in which to study nonequilibrium processes in enzymes and molecular motors (21)(22)(23)(24), and have been used by us to show how redoxcoupled proton pumping could be accomplished in principle (25). The model developed here is explicitly designed to reproduce known thermodynamic and kinetic properties of CcO.…”
mentioning
confidence: 99%
“…Recent singlemolecule (SM) experiments have shown that, with each stepping motion being strongly coupled to the ATP, the kinesin moves toward the (ϩ) ends of MTs by taking discrete 8-nm steps (3-7) in a hand-over-hand fashion (4,7,8). Although the ultimate understanding of kinesin's motility is still far from completion, the SM experiments (3)(4)(5)(6)(7)(8)(9), together with the series of kinetic ensemble measurements (10)(11)(12)(13) and theoretical studies (14)(15)(16)(17)(18)(19), begin providing glimpses to the physical principle of how kinesin walks.…”
Section: F Irst Recognized By Means Of Their Close Relationship Betweenmentioning
confidence: 99%